Pavel A. Florenskij : teólogo ortodoxo - Padrón, Héctor Jorge (2004)
Pavel A. Florenskij’s philosophical and theological beliefs have been subject to critical consideratíons which can and should be signalled with some serums and even harmful misconceptions. On the other hand, they have received their fair and necessary appreciation, given their valué and their influence on important developments in western philosophy and theology. The article examines the manifest oscilation oí this critique, and focuses on three main issues: (1) the question o í the epistolary style in “Stolp", (2) the question oí orthodox theodicy, and (3) the question oí a renewed reason in view o í the mystery of grief.